Recanalization of the Left Common Iliac Vein for May–Thurner Syndrome Associated with Arteriovenous Fistula. (2015) - Yuan, H.; Sun, J.; Qi, H.T.; Jin, X.; Wu, X.J.
Abstract : Introduction: Cases of May–Thurner syndrome associated with pelvic arteriovenous fistula (AVF) are uncommon. All the treatments reported are embolizations. The efficacy of recanalization of the left common iliac vein (CIV) in treatment of such cases is reported. Report: The case of a 78 year old man with co-existing May–Thurner syndrome and pelvic AVF confirmed by computed tomography angiography and arteriography is reported. Treatment by recanalization of the left CIV followed by a bare stent was selected instead of embolizing the AVF; a good result was obtained. Discussion: Recanalization of the left CIV by an endovascular technique can be an effective treatment for May–Thurner syndrome associated with AVF. Highlights: A patient with co-existence of May–Thurner syndrome and pelvic AVF is reported. Venous hypertension is a potential cause of acquired AVF. Recanalization of the left CIV can be a safe and effective treatment.